FlowCert : probabilistic certification for peer-to-peer computations - Varrette, S.; Roch, J. -L.; Leprevost, F. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2004)
Large scale cluster, peer-to-peer computing systems and grid computer systems gather thousands of nodes for computing parallel applications. At this scale, it raises the problem of the result checking of the parallel execution of a program on an unsecured grid. This domain is the object of numerous works, either at the hardware or at the software level. We propose here an original software method based on the dynamic computation of the data-flow associated to a partial execution of the program on a secure machine. This data-flow is a summary of the execution: any complete execution of the program on an unsecured remote machine with the same inputs supplies a flow which summary has to correspond to the one obtained by partial execution.